Danshen Injection inhibits peritoneal dialysis fluid-induced endothelial-mesenchymal transition in HMrSV5 cells by regulating the TGF-β/Smad signaling pathway - Yu, Lihua; Li, Jingya; Wang, Xiaoqi; Li, Li; Chen, Ya; Wang, Feiyu; Zhang, Kun; Wang, Tongsheng (Nan fang yi ke da xue xue bao = Journal of Southern Medical University, 2024)
To investigate the inhibitory effect of Danshen Injection on endothelial-mesenchymal transition (EndMT) induced by peritoneal dialysis fluid in HMrSV5 cells and the role of the TGF‑β/Smad signaling pathway in mediating this effect. HMrSV5 cells cultured in 40% peritoneal dialysis solution for 72 h to induce EndMT were treated with 0.05%, 0.1% and 0.5% Danshen Injection. CCK-8 assay was used to assess the changes in viability of the treated cells, and the levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β), and vascular endothelial growth factor (VEGF) in the cell supernatant were detected using ELISA; Western blotting was performed to detect the protein expressions of E-cadherin, α-smooth muscle actin (α-SMA), p-Smad 2/3, and Smad 7 in the cells. Culture in 40% peritoneal dialysis fluid for 72 induced significant EndMT in HMrSV5 cells, which exhibited obviously lowered cell viability. Danshen Injection within the concentration range of 0.025%-1.5% did not sign